2003
DOI: 10.1038/sj.mp.4001310
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of reelin as a candidate gene for autism

Abstract: Genetic studies indicate that chromosome 7q is likely to contain an autism susceptibility locus (AUTS1). We have followed a positional candidate gene approach to identify relevant gene(s) and report here the analysis of reelin (RELN), a gene located under our peak of linkage. Screening RELN for DNA changes identified novel missense variants absent in a large control group; however, the low frequency of these mutations does not explain the relatively strong linkage results on 7q. Furthermore, analysis of a prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 28 publications
2
80
0
1
Order By: Relevance
“…Several lines of evidence have since provided further support to this model: (1) the association between long RELN alleles and autism, almost entirely carried by Caucasian-American and not by Italian families in our initial study, 4 was independently replicated in two out of three studies assessing also simplex families in North America, [19][20][21] whereas no replication has been reported in European samples recruited in France, the UK, and Germany, 22,23 or in one US-based study assessing multiplex families only; 24 (2) a recent post-mortem study confirms and extends previous findings of decreased Reelin gene expression in autism, 11 reporting coincident changes in Reelin, Dab-1, and VLDL receptor gene expression in frontal cerebral and cerebellar cortices of brains from individuals with autism compared to age-, sex-, and post-mortem interval-matched controls; 25 (3) several epidemiological studies have recently found evidence of prenatal exposure to OP compounds in the USA, particularly for diazinon and chlorphyrifos, which have been most widespread in household use (see Discussion).…”
Section: Introductionmentioning
confidence: 84%
“…Several lines of evidence have since provided further support to this model: (1) the association between long RELN alleles and autism, almost entirely carried by Caucasian-American and not by Italian families in our initial study, 4 was independently replicated in two out of three studies assessing also simplex families in North America, [19][20][21] whereas no replication has been reported in European samples recruited in France, the UK, and Germany, 22,23 or in one US-based study assessing multiplex families only; 24 (2) a recent post-mortem study confirms and extends previous findings of decreased Reelin gene expression in autism, 11 reporting coincident changes in Reelin, Dab-1, and VLDL receptor gene expression in frontal cerebral and cerebellar cortices of brains from individuals with autism compared to age-, sex-, and post-mortem interval-matched controls; 25 (3) several epidemiological studies have recently found evidence of prenatal exposure to OP compounds in the USA, particularly for diazinon and chlorphyrifos, which have been most widespread in household use (see Discussion).…”
Section: Introductionmentioning
confidence: 84%
“…However, even the most frequently associated genes, such as RELN (reelin), 9 have negative replications reported. 10 Recently, the first genome-wide association study for ASDs has been published, implicating a number of genes and genomic regions, most significantly the area between cadherin genes CDH9 (cadherin 9) and CDH10 (cadherin 10) on chromosome 5p14.1. However, in this study, only a single SNP reached genome-wide significance after correction for multiple testing, confirming the difficulties involved in the identification of common variants contributing to ASD susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…region before the start codon, have reached conflicting results. [43][44][45][46][47][48][49] This may reflect only the common pattern of nonreplication of early claims from small studies 50 or a modest effect may still be present. A large study should be conducted on this association.…”
Section: Discussionmentioning
confidence: 99%